Criminologia feminista: uma análise do desenvolvimento de uma criminologia sob a crítica da teoria feminista no Brasil com especial foco na mulher transgressora brasileira - Lucca, Giovana (Universidade do Vale do Rio dos Sinos, 2020)
This research aimed to approach the development of feminist criminology, to understand how it can contribute to the effectiveness of fundamental rights of Brazilian women, with a special focus on incarcerated women. Through bibliographic research on criminology about its main Schools and theories, this work aims to demonstrate the attention given to gender issues by traditional criminology. In addition, the feminist theory was explored, as well as its aspects and achievements, showing that theory and social movements stand side by side and were fundamental in the achievement of rights. In addition, feminist epistemologies were approached, which represent criticisms of traditional research methods and law. Also, the means of social control over women, in a formal or informal way were researched, as well as the essential markers of analysis in the reality of Brazilian women. Furthermore, quantitative data from the prison system revealed the reality of the country and highlighted the treatment given to women in the Brazilian justice system. Through the analysis of the decision in the Habeas Corpus n. 143.641, by the Supremo Tribunal Federal, about the situation of incarcerated women, it was possible to demonstrate the main incidence of informal control means in formal control (justice system). Thus, it was shown that the justice system is not prepared to understand and attend the needs of women, neither to secure their fundamental rights, and that is why feminist criminology it crucial. Besides that, it is clear that there is an urgent need for Brazilian scientific research to increase efforts to research the issue of gender and so contribute to changing the treatment of women by law and the justice system, for the production and effective application of specific legislation, and the consequent abolition of sexist culture in the law field. Through the research, it was possible to conclude that there is a need for a solid development of Brazilian feminist criminology, considering specially the race and class markers, as well as that there is a need for the justice system to pay attention to the gender issue in order to secure women’s fundamental rights and thus structure a justice system prepared and alert to gender specificities.
Keywords: Criminologia; Mulher; Feminismo; Gênero; Cárcere; Criminology; Woman; Feminism; Gender; Imprisonment